Complete response of advanced HER2-amplified lung adenocarcinoma to cadonilimab combined with disitamab vedotin: a case report - Li, Yue; Ma, Keru; Wang, Hao; Liu, Zongying; Li, Zhuying (Frontiers in Oncology, 2025)
BackgroundHuman epidermal growth factor receptor 2 (HER2) gene amplification in lung adenocarcinoma is associated with aggressive tumor behavior and poor prognosis. Currently, there is no standard targeted therapy for HER2-amplified lung cancer.Case summaryA 60-year-old male presented with a mass in the right cervical spine area. Imaging and pathological examinations confirmed stage IV (T4N3M1) lung adenocarcinoma with metastases to both lungs, multiple lymph nodes, the pleura, the left adrenal gland, and the meninges. Genetic testing revealed HER2 gene amplification and low programmed death-ligand 1 (PD-L1) expression (tumor proportion score <1%). The patient declined conventional chemotherapy due to concerns about side effects. With his informed consent, he was treated with a combination of cadonilimab (a PD-1/cytotoxic T-lymphocyte antigen 4 bispecific antibody) and disitamab vedotin (an anti-HER2 antibody–drug conjugate), administered intravenously every 3 weeks. After nine treatment cycles over 6 months, imaging assessments showed complete disappearance of the pulmonary lesions, and the achieved complete response (CR) persisted for at least 7 months. The treatment was well-tolerated, and the patient maintained an excellent performance status (Eastern Cooperative Oncology Group score of 0) without significant adverse effects.ConclusionTreatment with cadonilimab and disitamab vedotin induced a sustained complete response in a patient with advanced HER2-amplified lung adenocarcinoma who declined chemotherapy. Thus, this combination therapy may offer a promising, effective, and well-tolerated treatment alternative for similar patients. Further clinical trials are warranted to validate these findings and potentially establish a new standard of care for this subset of lung cancer patients.